2020
DOI: 10.1155/2020/1015908
|View full text |Cite
|
Sign up to set email alerts
|

Intraplatelet L-Arginine-Nitric Oxide Metabolic Pathway: From Discovery to Clinical Implications in Prevention and Treatment of Cardiovascular Disorders

Abstract: Despite the development of new drugs and other therapeutic strategies, cardiovascular disease (CVD) remains still the major cause of morbidity and mortality in the world population. A lot of research, performed mostly in the last three decades, revealed an important correlation between “classical” demographic and biochemical risk factors for CVD, (i.e., hypercholesterolemia, hyperhomocysteinemia, smoking, renal failure, aging, diabetes, and hypertension) with endothelial dysfunction associated directly with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 105 publications
(108 reference statements)
0
18
0
3
Order By: Relevance
“…Animal protein provides greater amounts of essential amino acids, such as methionine and lysine, which have been reported to promote hypercholesterolemia in experimental animals [ 49 ]. Conversely, plant protein is rich in nonessential amino acids, including arginine, which may affect hypercholesterolemia via the L-arginine-nitric oxide pathway [ 50 ]. Another proposed mechanism is alteration in gut microbial composition in response to animal compared to plant protein supplementation in both human participants [ 51 ] and experimental animals [ 52 ], concurrently with changes in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Animal protein provides greater amounts of essential amino acids, such as methionine and lysine, which have been reported to promote hypercholesterolemia in experimental animals [ 49 ]. Conversely, plant protein is rich in nonessential amino acids, including arginine, which may affect hypercholesterolemia via the L-arginine-nitric oxide pathway [ 50 ]. Another proposed mechanism is alteration in gut microbial composition in response to animal compared to plant protein supplementation in both human participants [ 51 ] and experimental animals [ 52 ], concurrently with changes in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted using cultured human aortic vascular endothelial cells revealed that genistein enhances NO production via the PKA/CREB/eNOS/NO signaling pathway and plays a beneficial role in preventing hypertension [ 104 ]. Recent studies have shown the importance of the NO-mediated inhibition of CVDs [ 105 ], suggesting that genistein and daidzein possibly inhibit CVDs by inducing NO production in vascular endothelial cells. In addition, genistein suppressed superoxide production and NOX4 expression via ox-LDL in human umbilical vein endothelial cells [ 106 ].…”
Section: Effects Of Isoflavones On Metabolic Syndrome and Its Constituent Diseasesmentioning
confidence: 99%
“… 14 , 15 Furthermore, elevated intraplatelet ADMA concentration may result in impaired platelet-derived NO synthesis and subsequent increase in platelet activity. 16 …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Furthermore, elevated intraplatelet ADMA concentration may result in impaired platelet-derived NO synthesis and subsequent increase in platelet activity. 16 Next to NOS inhibitors, altered concentrations of NOrelated pathway metabolites may also play a role in endothelial dysfunction. Endothelial isoforms of NOS catalyse the conversion of L-Arg to NO.…”
Section: Introductionmentioning
confidence: 99%